Sovereignty through Interdependence - Gelber, Harry, (Amsterdamer Publikationen zur Sprache und Literatur ;, 1997)
Is it true that the forces of technology and interdependence have undermined the sovereignty of modern states? This book argues powerfully that the opposite is true: that over the past quarter century the major industrial states - the US, Britain, France, Germany and Japan - have mostly used these forces, often in novel ways, to pursue national purposes. The nation-state framework has, over that period, remained the basis of legitimate political authority and law. There has been a huge increase in the scope, incidence and detail of state regulation to manage, among other things, both the domestic economy and the effects of transnational flows. International management almost invariably depends upon state consent. The power of the state has never, anywhere, been absolute and its methods of management have always been changeable. But there is no evidence that its managerial effectiveness has, overall, been less in 1995 than in 1975 or 1965. This book therefore takes strong issue with much of the literature on interdependence and international organisation which has appeared in recent times. It is especially useful for those trying to understand the larger framework within which business must operate or the sources of authority for anyone's plan to manage problems of financial or population flows, of transnational conservation problems or of trade. The book will also be of particular use in graduate and senior undergraduate courses in international relations or organisation.